PENGARUH KOSA KATA BAHASA INGGRIS, DASAR KOMPUTER DAN AKUNTANSI TERHADAP PRESTASI BELAJAR MYOB - Darojatun Yakti Pradhana; Lyna Latifah (Dinamika Pendidikan)
The purpose of this study was to determine the influence either partially or simultaneously of English vocabulary mastery, basic computer and basic accounting toward the learning achievement of MYOB accounting computer at class XI Accounting Skills Competency at SMK N 1 Bawang in the academic year of 2011/2012. The population of the study was 94 students and they were all the respondents. The data were collected by test and documentation. Then, the data were analyzed by percentage descriptive analysis and multiple linear regression analysis. The result of the study showed that simultaneously, English vocabulary mastery, basic computer and basic accounting influenced the learning achievement significantly for 23.7%, partially English vocabulary mastery influenced the MYOB accounting computer learning achievement for 7.95%, basic computer mastery influenced it for 5.15%, and basic accounting mastery influenced it for 7.51%. It means that the good mastery of English vocabulary, basic computer and basic accounting can improve the learning achievement of MYOB accounting computer.